SISTEM INFORMASI DATA WARTAWAN MENGGUNAKAN VISUAL BASIC 6.0. (STUDI KASUS HARIAN PAGI JAMBI EKSPRES): Visual Basic;Payroll;Jambi Express Employees. - Mulyadi; Asyhadi, Ahmad (LP2M Universitas Nurdin Hamzah, 2022)
The information system for journalists at the Jambi Ekspres Morning Daily initially used an agenda or manual system. With the development of the organizational structure, it becomes bigger and the problem becomes even bigger if a fixed and systematic information system is not used. The change from the old system to a new system, namely a computerized system, makes work faster and produces more accurate reports to support a fast-growing organization.The author here designs an application program that uses visual basic 6.0 with a new design in terms of processing news data to make a journalist professional allowance report at the editorial secretariat of the Jambi Express Daily Morning. The author hopes that the management and secretariat of the editorial secretariat of the Jambi Express Daily Morning can optimize existing facilities to implement a more efficient and effective work system.